Larger size ratio associated with the rupture of very small (≤3 mm) anterior communicating artery aneurysms. (23rd March 2016) - Xu, Ting; Lin, Boli; Liu, Shuailiang; Shao, Xiaotong; Xia, Nengzhi; Zhang, Yue; Xu, Haoli; Yang, Yunjun; Zhong, Ming; Zhuge, Qichuan; Zhao, Bing; Chen, Weijian
Abstract : Background: Anterior communicating artery (AcoA) aneurysms have a high rupture risk, and ruptured AcoA aneurysms tend to be smaller than other intracranial aneurysms. We aimed to determine the incidence and morphologic predictors of aneurysm rupture of very small AcoA aneurysms. Methods: We conducted a retrospective analysis of 519 consecutive patients with single AcoA aneurysms between December 2007 and February 2015 in our hospital. Aneurysm morphologies were re-measured using CT angiography images. Very small aneurysms were defined as those with a maximum size ≤3 mm, and small aneurysms were defined as those with a maximum size ≤5 mm. Multivariate regression analyses were used to determine the association between aneurysm morphology and aneurysm rupture status. Results: Of the 474 ruptured AcoA aneurysms, 134 (28.3%) aneurysms were very small and 278 (58.6%) aneurysms were small. In the univariate analysis for very small aneurysms, larger aneurysm size (p=0.037), larger size ratio (p=0.002), higher aneurysm height (p=0.038), smaller vessel size (p=0.012), and dominant A1 segment configuration (p=0.011) were associated with aneurysm rupture. Multivariate analysis revealed that a larger size ratio was independently associated with the rupture status of the very small aneurysms (OR 3.69, 95% CI 1.5 to 9.0; p=0.004), and larger aneurysm size, larger size ratio, and dominant A1 segment configuration were associated with the rupture of small aneurysms. Conclusions: About one-third of ruptured AcoA aneurysms were very small. A larger size ratio, rather than other aneurysm morphologies, was independently associated with the rupture of very small AcoA aneurysms.